Corporate Governance and Company Value: A Manufacturing Industry Case Study - Helma Malini; Dyen Natalia; Giriati Giriati (Forum Inovasi Bisnis dan Manajemen, 2021)
The purpose of this research is to look into the impact of corporate governance in the Indonesia Stock Exchange's Manufacturing Industry. Panel data from 73 Manufacturing Industry companies on the Indonesia Stock Exchange from 2014 to 2018 with a total of 365 observations of data whose research results were analyzed using panel data regression analysis with the Random Effect Model approach. Institutional ownership has a positive effect on Tobin's q and market book value, according to the study's findings. Tobin's q and market book value are negatively affected by foreign ownership. Meetings of the Board of Commissioners and the Audit Committee have a negative impact on stock price returns. Meetings of the board of directors, audit committee, and board of commissioners were found to have no impact on the value of the company. On the basis of these findings, it can be concluded that the results of testing the independent variables on the dependent are inconclusive and should be questioned further.